TELAAH ISU CHILDFREE DALAM PERSPEKTIF MA'NA CUM MAGHZA: STUDI HERMENEUTIKA KONTEMPORER - Wilianca, Dea Ananda; Fawwaz, Muhammad; Arif, Muhammad Hafizi Zul; Masyhur, Laila Sari (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The phenomenon of "childfree" is increasingly popular in modern society, especially among young couples, and has become a relevant topic for study. The decision to remain childless is often influenced by factors such as economic pressures, career instability, and the desire for personal growth or educational pursuits. This study examines the childfree issue through a contemporary hermeneutical approach, specifically employing the Ma’na Cum Maghza method developed by Sahiron Syamsuddin. This method balances the literal meaning of texts with the main message derived from them, applying these insights to modern social contexts. In Indonesia, the childfree phenomenon is often linked to early marriage practices, which significantly impact the physical and mental well-being of individuals. Despite being regulated by law, early marriage reveals a shift in societal views on family roles and reproduction. Through the Ma’na Cum Maghza approach, this research underscores the importance of interpreting religious texts not only for their literal meanings but also by contextualizing their messages in response to contemporary challenges. This approach provides fresh insights into understanding modern issues like childfree, highlighting the relevance of contemporary exegesis in addressing current socio-religious challenges.